Temperature and light intensity effects on photodegradation of high-density polyethylene. (July 2019) - Fairbrother, Andrew; Hsueh, Hsiang-Chun; Kim, Jae Hyun; Jacobs, Deborah; Perry, Lakesha; Goodwin, David; White, Christopher; Watson, Stephanie; Sung, Li-Piin
Abstract: The photodegradation of polymers poses a serious challenge to their outdoor application, and results in significant financial loss due to early or unexpected system failure. A better understanding of their degradation kinetics aids the improvement of materials and systems. However, most work to date on many polymeric materials focuses on only one or a few exposure conditions which are pertinent to typical environmental ambients. Here the model polyolefin system of high-density polyethylene (HDPE) was exposed under controlled laboratory conditions to a range of temperatures (30 °C, 40 °C, 50 °C) and ultraviolet (UV) light intensities (153 W m −2, 61 W m −2, 38 W m −2, 15 W m −2, 8 W m −2, and 0 W m −2 ). Changes to the mechanical, chemical, and structural properties were monitored by uniaxial tensile testing and Fourier-transform infrared spectroscopy (FTIR), which showed that the rapid embrittlement of HDPE was concurrent with increases in yield strength, stiffness, oxidation, and crystallinity. The rates of change tended to increase under more aggressive exposure conditions, and the photothermal activation energies and UV dose-damage relationships for these properties were determined. A comparison to HDPE under outdoor exposure in southern Florida shows a similar magnitude of material change up to the point of embrittlement, despite the differences in spectral irradiance and the constantly changing outdoor conditions. These results quantify the effect of temperature and UV light intensity on the photodegradation of HDPE and can be utilized to develop stabilization strategies for these and related thermoplastic materials. Graphical abstract: Image 1 Highlights: Accelerated and natural weathering of high-density polyethylene showed an abrupt transition to brittle mechanical failure. Accelerated weathering at various temperatures and ultraviolet light intensities. Kinetic and dose-damage relationships for mechanical, chemical, and structural properties were determined.